2022
DOI: 10.3389/fbioe.2022.927248
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Substrates Promote the Differentiation of Inner Ear Lgr5+ Progenitor Cells Into Hair Cells

Abstract: The ideal treatment for sensory hearing loss is to regenerate inner ear hair cells (HCs) through stem cell therapy, thereby restoring the function and structure of the cochlea. Previous studies have found that Lgr5+ supporting cells (SCs) in the inner ear can regenerate HCs, thus being considered inner ear progenitor cells. In addition to traditional biochemical factors, physical factors such as electrical conductivity also play a crucial role in the regulation of stem cell proliferation and differentiation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that the combination of graphene oxide and hydrogels can promote the expansion of SGN growth cones and the outgrowth of neurites (Shi et al, 2023). Graphene substrates have also been revealed to promote the proliferation and HC differentiation of inner ear Lgr5+ progenitor cells, despite having no effect on cell viability (Ding et al, 2022). MXene, an emerging two-dimensional layered material with a structure similar to that of graphene, has been used in a wide range of applications since its discovery (Naguib et al, 2011) due to its excellent hydrophilicity and electrical conductivity (Naguib et al, 2021).…”
Section: Conductive Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the combination of graphene oxide and hydrogels can promote the expansion of SGN growth cones and the outgrowth of neurites (Shi et al, 2023). Graphene substrates have also been revealed to promote the proliferation and HC differentiation of inner ear Lgr5+ progenitor cells, despite having no effect on cell viability (Ding et al, 2022). MXene, an emerging two-dimensional layered material with a structure similar to that of graphene, has been used in a wide range of applications since its discovery (Naguib et al, 2011) due to its excellent hydrophilicity and electrical conductivity (Naguib et al, 2021).…”
Section: Conductive Nanomaterialsmentioning
confidence: 99%
“…CI technology has restored partial hearing in patients with SNHL over the past few decades; however, challenges still remain (Naples and Ruckenstein, 2020). Research on coating materials for CI electrodes has never stopped, and these coating materials, especially topologically structured (Clarke et al, 2011;Tuft et al, 2014a;Mattotti et al, 2015;Cai et al, 2016;Leigh et al, 2017;Xu et al, 2018;Truong et al, 2021) or conductive materials (Wei et al, 2021;Ding et al, 2022;Hu et al, 2022;Liao et al, 2022;Zhang et al, 2022), can be used as interfaces to promote axonal regrowth of degenerated SGNs.…”
Section: Biomaterials-based Coating For CI Interfacesmentioning
confidence: 99%
“…Ding et al demonstrated that graphene can induce the differentiation of inner ear progenitor cells into hair cells without the use of chemical factors. 32 Myosin7a+ cells were observed to be more prevalent on graphene substrates than on TCPS, suggesting that graphene may facilitate the differentiation process. In another study, computer simulations have also shown that the electric field on graphene, with a surface charge density of approximately −4 × 10 −4 C/m 2 , is nearly 2−3 times higher than that on TCPS (graphene, 0.8 V/μm; TCPS, 0.1 V/μm).…”
mentioning
confidence: 96%
“…One possible mechanism is that the electrical properties of graphene may enhance the maturity of inner ear organoids. Ding et al demonstrated that graphene can induce the differentiation of inner ear progenitor cells into hair cells without the use of chemical factors . Myosin7a+ cells were observed to be more prevalent on graphene substrates than on TCPS, suggesting that graphene may facilitate the differentiation process.…”
mentioning
confidence: 99%